An Improved of Channel Allocation for WLAN Using Vertex Merge Algorithm - Mr, Handrizal; Mr, Muhammad Zarlis; Noraziah, Ahmad; Abdalla, Ahmed N. (2012)
Graph colouring is a useful algorithm for channel allocation on wireless local area network (WLAN). Through this algorithm, each access point (AP) that adjacent will be given different channels based on colours available. Degree of saturation (Dsatur) is the popular algorithms being used for channel allocation in this domain. However, this algorithm has its weaknesses in terms of minimum number of channel required. In this study, channel allocation called Vertex Merge Algorithm (VMA) is proposed by considering only channel allocation on WLAN. It is based on logical structure of vertex/access point in order to a colouring the graph. Each vertex on the graph will be arranged based on decreasing number of degree. The vertex in the first place on the set will be given a colour, and then these vertices are merged with not adjacent vertex. This process will be continued to repeat until all vertices are given colour. The assignment provides a minimum number of channels required. A series of experiment was carried out by using one computer. Vertex Merge Algorithm (VMA) simulation is developed under Linux platform. It was carried out in PHP programming integrated with GIMP for open and edit image. The experimental results showed that the proposed algorithm work successfully in channel allocation on wireless local area network (WLAN) when no failures occurred.